The Elephant in the Room: Animal Value(s) within and beyond Necropolitics in The Only Harmless Great Thing (ENTHYMEMA, 2025)
This essay investigates the conflictual and oppressive relationship between humans and animals in the context of late capitalism in ‘western/ized’ societies and how speculative fiction can imagine and inspire alternative ways for interspecies coexistence. It focuses especially on the representation of animal labor, i.e. the way animals are involved in the contemporary production system. The essay takes Brooke Bolander’s 2018 novella The Only Harmless Great Thing as a case study, analyzing it through the lens of Achille Mbembe’s necropolitics (2003), and arguing that the author provides an attempt at ‘necropolitical and post-necropolitical imagination’ that, despite not always being successful, shows how to envision an alternative future without straying too far from the present.
Keywords: Speculative fiction; Animals; Necropolitics; Capitalism; Animal Labor